From a Novice Teacher to a Teacher Leader: An English-As-a-Foreign-Language (EFL) Teacher’s Cognitions About Her Professional Development - Gao, Lori Xingzhen; Yang, Jennifer Jie (Frontiers in Psychology, 2022)
In this paper, a qualitative study was conducted on Jennifer, an EFL teaching professional at the tertiary level in a Chinese context, to investigate her cognitions regarding her professional development and accompanying facilitating factors in her journey from a novice teacher to a teacher leader with Borg’s model of language teacher cognition as the conceptual basis for subsequent analysis. Jennifer’s written overview and verbal narration in interviews of her journey in professional development were gathered following guiding protocols. Collected data were processed with thematic analysis in NVivo 12. Findings suggest that Jennifer has clear cognitions about how she learned and improved, i.e., the positive changes, in her professional journey and the facilitating factors that mediated her improvement and progress. These facilitating factors were found to include her teaching experience, in-service training, administrative promotion, drawing wisdom from reading Chinese classics, and constant reflection upon her EFL teaching, etc. The implications of the present study for language teacher cognition researchers, English language teacher educators, and EFL teachers in the Chinese context were also discussed.